Forecasting the price of the cryptocurrency using linear and nonlinear error correction model - Jong-Min Kim; Chan Ho Cho; Chulhee Jun (Journal of Risk and Financial Management, 2022)
We employed linear and nonlinear error correction models (ECMs) to predict the log returns of Bitcoin (BTC). The linear ECM is the best model for predicting BTC compared to the neural network and autoregressive models in terms of RMSE, MAE, and MAPE. Using a linear ECM, we are able to understand how BTC is affected by other coins. In addition, we performed Granger-causality tests on fourteen cryptocurrencies.
Keywords: 330; cryptocurrencies; Bitcoin; error correction model; Granger causality